Endovascular Management of Cerebral Bypass Graft Problems: An Analysis of Technique and Results - Ramanathan, D.; Ghodke, B.; Kim, L.J.; Hallam, D.; Herbes-Rocha, M.; Sekhar, L.N. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Cerebral bypass grafts may develop generalized graft narrowing or focal stenosis during the perioperative period or later. Endovascular techniques such as PTA and stent placement of graft vessels are potential treatment options. Our objective was to review the safety, indications, technique, and results of endovascular management of graft problems. MATERIALS AND METHODS: All patients with cerebral bypass procedures by using graft vessels from 2005 to 2009 were identified from a prospective registry and were studied retrospectively. Patient characteristics, bypass procedures, indications for endovascular interventions, graft patency, and clinical outcomes were reviewed from medical charts and imaging records. RESULTS: A total of 79 patients underwent bypass procedures by using graft vessels. Seven patients of this group underwent endovascular interventions for the treatment of graft narrowing. Four of the 7 patients were treated for graft narrowing in the perioperative period (<1 month) with PTA; and 3 of the 7 patients, for late stenosis, 2 with PTA alone and 1 with PTA followed by stent placement. All procedures were immediately successful in improving flow through the graft. In late stenosis, PTA alone provided temporary improvement followed by recurrence, whereas PTA with a stent procedure was effective in the 1 patient long term. CONCLUSIONS: PTA is safe and effective in the management of graft spasm in the perioperative period. For late graft stenosis, PTA alone provides only temporary respite, while PTA with stent placement may be an effective solution. ATAanterior tibial arteryECAexternal carotid arteryECICextracranial– to intracranialIADSAintra-arterial digital subtraction angiographyICintracranialICAinternal carotid arteryMCAmiddle cerebral arterymRSmodified Rankin ScalePCAposterior cerebral arteryPTApercutaneous transluminal angioplastyRAGradial artery graftSVGsaphenous vein graftVAvertebral artery